Potensi Populasi Infusi Genetik untuk memperluas variasi genetik kebun benih semai Pinus merkusii di Jember - ILG Nurtjahjaningsih (Jurnal Pemuliaan Tanaman Hutan, 2009)
When genetic base in a seed orchard is narrow, a startegy of genetic infusion should be applied to broaden and maintain its ganetic variation over several successive generations. For this purpose, genetic-infusion populations were established in tree improvement programs of Pinus merkusii located in jember. To be successful genetic variation of the infusion populations should be assessed. This study was aimed to determine genetic diversity of three infusion populations of P merkusii i.e. Takengon, janto and Blankejeren population using five microsatellite markersi. The results  showed that gene diversity of plus trees in the seed orchard was  at a moderate level (HE=0.508).Significant inbreeding deviation from the Hardy-Weinberg equilibrium (HWE) was detected (FIS = 0.073). Gene diversity of the infusion populations was comparatively high. It ranged between 0.498 (Janto) and 0.524 (Blankejeren). The FIS was low and insiqnificant deviation from HWE at any genetic infusion populations. The genetic differentiation among the populations (in both seed orchard and genetic infusion) was very low (FST=0.003) indicating that they were genetically related. It is recommended that the infusion populations have a potential to maintain to genetic diversity in the seed orchard.However, Since they are related, it is necessary to find other potential genetic infusion populations that could broaden genetic diversity more effectively in the seed ochard.